Avaliação da qualidade da Atenção Primária à Saúde no município de Sobral, Ceará a partir do QualiAB - Barreto, Raissa Mont´Alverne (2019)
Primary Care has Family Health as a priority strategy for its organization, with indisputable advances, but there are still many problems that need to be addressed so that it can play its role as coordinator of health care. Thus, the need to carry out evaluative quality surveys of Primary Health Care emerges due to its capillarity of actions aimed at the majority of the population. The objective of this study was to evaluate the quality of Primary Care of the city of Sobral, Ceará within the dimensions Structure and Process, from the Donabedian referential. It is an evaluative research under the quantitative and qualitative approaches. For the collection of the quantitative data an adaptation of the Instrument of Evaluation of Basic Attention Services (QualiAB) with the managers and teams of health of the family, was inserted in a free software of web platform called LimeSurvey. For the qualitative data, semi-structured interviews were conducted with managers of the Units in order to collect information about the perception of these actors regarding the evaluation process and possible impacts resulting from this process. To analyze the qualitative data, a Bardin content analysis was performed with the support of the software N Vivo11, and for the analysis of the quantitative data the QualiABSobral tool was built, which was developed in a web platform and fed by importing the data inserted in the software used to collect the data. Simple descriptive statistics techniques were also used, from tabulation, data processing and table production by the Excel program. In general, for the structure dimension, good performance was observed, but it is worth emphasizing aspects that compromise this assistance, such as the fact that three Units are without a doctor and 50% of them present a smaller number of teams than the one recommended by PNAB, in high care demands. In addition, it was visualized the need for improvements in accessibility for people with disabilities; insufficient emergency and emergency equipment; absence of vehicle for use by the Unit; and deficiency in the availability of some drugs. For the process dimension, good results were observed, but it is necessary to reflect on the scheduling of the consultations; waiting time between referrals, specialist consultations and examinations; routine care of the child; greater emphasis on health care for man and the worker; and strategies to stimulate popular participation. The results of the interviews with the managers brought qualitative contributions and allowed identifying factors that deserve to be highlighted for the improvement of the quality of care, such as a greater valuation of the evaluation processes to contribute to the planning and management of the local health system in an efficient, and satisfactory; greater commitment between Primary Care and Health Care Networks to simplify and make effective the counterreference process in order to value the continuity of care; minimization of bureaucratic processes linked to management and simplification in filling spreadsheets to generate health indicators that are compatible between services. Thus, the results allow obtaining information essential to strategic decision making by managers and a broader picture of the actual situation of Sobral, besides contributing to the elaboration of a planning based on the needs and propositions of improvements for the qualification of the assistance rendered to the population of the studied municipality.